1996
DOI: 10.1111/j.1574-6968.1996.tb08027.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and some properties of streptococcal NAD-glycohydrolase

Abstract: NAD‐glycohydrolase (NADase) was purified from culture supernatant fluids of group C streptococci by adsorption on silica gel, chromatography on hydroxyapatite and ion exchange on Mono S column. After inactivation of a chymotrypsin‐like protease, a homogeneous enzyme was isolated with an N‐terminal sequence of VSGKEGKKSDVKYEMTKVMEANATSS‐KEDKHVMHTLDKVM. According to serological methods, the purified enzyme of group C streptococci was identical to the group A enzyme showing a specific activity of 10000000 U mg−1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…The kinetic parameters for the ␤-NAD ϩ glycohydrolase reaction were determined using a sensitive HPLCbased assay (Table 1). The observed turnover number for SPN (Table 1) was similar to that determined for a related ␤-NAD ϩ glycohydrolase purified from a group C streptococcal species (12,000 s Ϫ1 ) (35). Comparison of this value to the reported k cat for the ADP-ribosyltransferase diphtheria toxin fragment A (0.0083 s Ϫ1 ) (33) shows the turnover number for SPN is ϳ1 ϫ 10 7 -fold higher, suggesting the activity may resemble that of the strict ␤-NAD ϩ glycohydrolases and not that of ADP-ribosyltransferases.…”
Section: Kinetic Parameters For Spn Hydrolysis Of ␤-Nadsupporting
confidence: 75%
See 1 more Smart Citation
“…The kinetic parameters for the ␤-NAD ϩ glycohydrolase reaction were determined using a sensitive HPLCbased assay (Table 1). The observed turnover number for SPN (Table 1) was similar to that determined for a related ␤-NAD ϩ glycohydrolase purified from a group C streptococcal species (12,000 s Ϫ1 ) (35). Comparison of this value to the reported k cat for the ADP-ribosyltransferase diphtheria toxin fragment A (0.0083 s Ϫ1 ) (33) shows the turnover number for SPN is ϳ1 ϫ 10 7 -fold higher, suggesting the activity may resemble that of the strict ␤-NAD ϩ glycohydrolases and not that of ADP-ribosyltransferases.…”
Section: Kinetic Parameters For Spn Hydrolysis Of ␤-Nadsupporting
confidence: 75%
“…7). This was an unexpected result, because the ␤-NAD ϩ glycohydrolases from the related group C streptococcal species do not hydrolyze ␤-NADP ϩ (35). However, analysis of Michaelis-Menten parameters revealed that NADP ϩ is a poor substrate for SPN with an apparent K m of 1.7 Ϯ 0.4 mM and observed k cat of 384 Ϯ 56 s Ϫ1 .…”
Section: Spn Lacks ␤-Nadmentioning
confidence: 96%
“…Genetic and functional investigations of these inhibitors have not yet been performed. On the other hand, hemolytic streptococci secrete thermolabile NADase into culture medium (27)(28)(29). Streptococcal cells producing the extracellular NADase contain an inhibitor protein against this enzyme (30).…”
Section: Discussionmentioning
confidence: 99%
“…NADase Assay-The NADase assay was performed by using the method of Gerlach et al (29). One unit of the enzyme cleaves 1 mol of NAD in 1 min at 37°C.…”
Section: Purification Of His Tag-fused Orf1-the Bugbuster Extract Of mentioning
confidence: 99%
“…NAD-glycohydrolase was previously puri¢ed from group C streptococci and its N-terminal sequence determined [18]. This sequence (40 amino acids) was used to search the S. pyogenes strain SF370 genome database (www.genome.ou.edu).…”
Section: Identi¢cation Of the Gene That Encodes Nad-glycohydrolase Ofmentioning
confidence: 99%